Application of simplified operating deflection shape technique in machinery vibration assessment / Mohd Bakar Mohd Mishani - Mohd Bakar , Mohd Mishani (2017)
Machines are designed to help and improve human daily work load. The availability of machines make daily work can be performed faster, easier, safer and in a large scale. It is natural for any operated machines to produce vibration due to its moving part. Some of this vibration can be acceptable and some are harmful to human body if exposed to this machinery vibration for a long period. Because of this, it is crucial to investigate and assess machinery vibration to determine the machines condition and its minimal exposure to human body. Researchers have put an effort to develop an advanced method to perform this machinery vibration assessment. Current machinery vibration assessment requires highly skilled and trained personnel to be able to perform the vibration data analysis. Therefore, a simplified technique through the application of operating deflection shape (ODS) analysis is proposed to reduce the time required for performing vibration data acquisition and analysis. This study was divided into 2 main parts which are assessment on rotating machinery and assessment on reciprocating machinery. The first part of this study is to test the effectiveness of the simplified technique in a laboratory condition before being applied in real industrial case studies. The second part is to test the application on reciprocating motion of an air compressor before being applied on bio-fuel powered diesel engine to determine optimum bio-fuel blend. The results on rotating machinery vibration assessment show vibration data acquisition is more efficient and time saving by using tri-axis accelerometer and relative phase technique. Furthermore, analysis and machinery fault can be identified effectively and faster through visualising the machine motion using a simplified ODS technique. This simplified technique is seen as practical approach to be proposed and integrated into conventional machinery vibration assessment. Meanwhile, the results on diesel engine vibration assessment show optimum bio-fuel blend can be determined faster and easier by using the proposed technique which consists of time domain analysis, frequency domain analysis and motion visualisation analysis / ODS analysis. The time domain and frequency domain analysis is first performed to minimise the effect of external vibration source due to torque before studying the performance of bio-fuel blends in a single-cylinder 4-stroke diesel engine. It is observed that bio-fuel powered engine at full speed with the lowest engine torque is more suitable to be used in identifying optimum fuel blend with minimal engine vibration. Bio-fuel blend B20 has the minimal vibration in overall RMS acceleration at full speed compared to other bio-fuel blends.